4q27 as a psoriasis susceptibility locus in the Northeastern Chinese Han population. Issue 1 (11th December 2014) - Zhou, J.; Wang, L.; Wang, F.; Xu, P.; Li, Y.; Bai, B.; Dang, L.; Sun, D.
Abstract Psoriasis is an autoimmune inflammatory skin disease with genetic components. Chromosome 4q27 is related to many autoimmune diseases, however, the relationship between psoriasis and 4q27 has not been fully established yet. The objective of this study is to investigate the association between chromosome 4q27 and psoriasis in the Northeastern Chinese Han population. Four common single nucleotide polymorphisms (rs2069762, rs4833837, rs6840978, and rs7684187) from chromosome 4q27 were genotyped in 400 psoriasis cases and 398 controls from the Northeastern Chinese Han population using the Multiplex SNaPSHOT method. Single nucleotide polymorphism and haplotype frequencies were analyzed using spss 13.0. Our data indicated that rs2069762 GG, TG genotypes [GG: odds ratio (OR) = 2.6875, 95% confidence interval (CI) = 1.5948–4.5290, P < 0.0001; TG: OR = 1.6159, 95% CI = 1.2044–2.1681, P = 0.0013], and H3 haplotype (OR = 1.717, 95% CI = 1.050–2.808, P = 0.030) increased the risk of psoriasis. Furthermore, rs4833837 GG, GA genotypes (GG: OR = 0.2071, 95% CI = 0.0685–0.6266, P = 0.0022; GA: OR = 0.4711, 95% CI = 0.3289–0.6746, P < 0.0001), and H5 haplotype (OR = 0.482, 95% CI = 0.238–0.978, P = 0.039) were identified as protective factors for psoriasis. 4q27 polymorphisms are associated with psoriasis in the Northeastern Chinese Han population.